“Not A Thing?” Rogers Brubaker’s Trans: Gender and Race in an Age of Unsettled Identities and Its Relevance for Central and Eastern Europe - Kováts, Eszter (Identities: Journal for Politics, Gender and Culture, 2019)
Author(s): Eszter Kováts Title (English): “Not A Thing?” Rogers Brubaker’s Trans: Gender and Race in an Age of Unsettled Identities and Its Relevance for Central and Eastern Europe Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 124-130 Page Count: 7 Citation (English): Eszter Kováts, “‘Not A Thing?’ Rogers Brubaker’s Trans: Gender and Race in an Age of Unsettled Identities and Its Relevance for Central and Eastern,” Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019): 124-130.